2017
DOI: 10.3390/molecules22030488
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Momordica charantia (Bitter Melon) on Ischemic Diabetic Myocardium

Abstract: Objective: A rat model is here used to test a hypothesis that Momordica charantia (Bitter melon (BM)) extract favorably alters processes in cardiovascular tissue and is systemically relevant to the pathophysiology of type 2 diabetes (T2DM) and related cardiovascular disease. Methods: Male Lean and Zucker Obese (ZO) rats were gavage-treated for six weeks with 400 mg/kg body weight bitter melon (BM) extract suspended in mucin–water vehicle, or with vehicle (Control). Animals were segregated into four treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…It was also reported that M. charantia acts as an antihypertensive agent, nevertheless this was not completely investigated [39]. Another study showed that bradycardia was observed in Zucker Obese (ZO) rats upon consumption of M. charantia [40]. Conversely, some studies reported slight increase of heart rate in the group of lean rats upon the consumption of this extract [40].…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that M. charantia acts as an antihypertensive agent, nevertheless this was not completely investigated [39]. Another study showed that bradycardia was observed in Zucker Obese (ZO) rats upon consumption of M. charantia [40]. Conversely, some studies reported slight increase of heart rate in the group of lean rats upon the consumption of this extract [40].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus, one of the fastest growing diseases in the world, is a group of metabolic diseases characterized by hyperglycemia resulting from defects in insulin secretion, insulin action, or both [ 96 ]. Many studies suggest that a variety of M. charantia extract can be used as a remedy for the treatment of diabetes [ 8 , 31 , 97 , 98 , 99 , 100 , 101 ]. It has also been widely used as an antidiabetic drug in different countries for thousands of years [ 8 , 10 , 102 ].…”
Section: Biological Activitiesmentioning
confidence: 99%
“…MC is a herbal plant which is usually recommended for treatment of many diseases, particularly diabetes. However, some studies showed that despite the diverse beneficial effects of MC ( Bai et al, 2016 ; Czompa et al, 2017 ), it has a detrimental role on the reproductive system of male rats ( Tumkiratiwong et al, 2014 ). The results of the present investigation showed no significant effects on the reproductive capability that is governed by photoperiods in male golden hamsters.…”
Section: Discussionmentioning
confidence: 99%